Dynamical analysis of freeway traffic - Lino Figueiredo (2004)
The paper presents the simulator of intelligent transportation systems (SITS). The SITS is based on a microscopic simulation approach to reproduce real traffic conditions in an urban or nonurban network and considers different types of vehicles, drivers, and roads. A dynamical analysis of several traffic phenomena is then addressed. The results of using classical system theory tools notes that it is possible to study traffic systems, taking advantage of the knowledge gathered with automatic control algorithms. In this line of thought, a new modeling formalism based on the embedding of statistics and Fourier transform is also presented.